Anda di halaman 1dari 4

# ASSIGNMENT – 5

## (1). (a)As the polar decomposition theorem states that deformation

gradient F = RU =VR
t
0 F = 0 tR . 0 tU = 0 tV . 0 tR
Where 0tF is the orthogonal rotation tensor
t
0 U , 0tV are the symmetric and positive definite right and left
stretch tensors respectively
We know that, symmetric tensors have real distinct eigenvalues λi , i = 1,2,3 with
associated eigenvectors (principal axes)
So, 0
t
U . 0ni = λi . 0ni
t
By applying a rotation 0 R
λi . 0tR . 0ni = 0tR . 0tU . 0ni
= 0 t R . 0 t U . 0 ni
= 0tV . 0tR . 0ni
t
= 0 V . 0 t R . 0 ni
= 0 t V . t ni
= λi . tni
It’s clear that the right and left stretch tensors are similar i.e, they have the same
eigenvalues but rotated axes
As tni = 0tR . 0ni
(b) From matrix analysis, singular value decomposition theorem (i.e, polar
decomposition for square matrix) states that Ǝ matrices q, ᴧ, r such that [F] =
[q][Λ][r]
Where
[q] and [r] are orthogonal
[Λ] is “pseudo-diagonal” (i.e., wheneverΛij=0 if i j)
[Λ] is positive semi-definite in the sense that it’s diagonal
Components, are non-negative.

As [q] [q]T = I
[F] = [q] [Λ] [q]T [q] [r]
[F] = [V] [R] as [q] [Λ] [q]T = [V] ; [R] = [q] [r]
As [r] [r]T = [r]T [r] = I
[F] = [q] [r] [r]T [Λ] [r] as [r]T [Λ] [r] = [U]
[F] = [R] [U]
Here note that R is itself orthogonal and [U], [V] are symmetric and positive
definite of right and left stretch respectively. And these give non-singular tensor.
To satisfy
[V] [R] = [R] [U] = [F] , it’s clear that that the values of U ,R, V are unique and
these give unique F tensor
So, polar decomposition of F is unique.

2.
• SIMPLE SHEAR:
Given F = ( )

• FT =
• FT *F = ( )

• FT*F = U2 = -------------(1)
• E = ½ (FT *F - I ) = ½ []
• E = ½ []
• We know U = I +E =
• U=
• U-1 = I – E =
• U-1 =
• We know F = RU
• R = FU-1 = ( )*
• R=
• F = VR
• V = FR-1
• V = ( )* 1/

ALTERNATE METHOD:

For calculating U we find eigenvalues and its vector from equation (1)

## For eigenvalues |U2- 𝜆𝐼| = 0

1-λ ϒ 0

ϒ (ϒ ∗ ϒ)+1- λ 0 = 0

0 0 1- λ

## (1- λ)[1+(ϒ ∗ ϒ) − λ](1- λ) – (ϒ ∗ ϒ ∗ (1 − λ)) = 0 λ2 – λ(ϒ2+2)+1

= 0 and λ = 1
• λ = 1, ½[ϒ2± (ϒ(ϒ2+4)1/2+2)]

For λ1 = 1

• e1 = = e3

## For λ2 = ½[ϒ2+ (ϒ(ϒ2+4)1/2+2)]

For λ3 = ½[ϒ2- (ϒ(ϒ2+4)1/2+2)]

• e2 = = e1 + ( )e2
• e3 = = e1 + ( )e2
we know that for U and U2 eigenvectors are same and eigenvalues of U2 is square of eigenvalues
of U.

• U=1e